DEVOTION TO PARENTS IN ISLAM - Abdul Aziz Romdhoni (Values: Jurnal Kajian Islam Multidisiplin, 2024)
Children are a source of happiness and comfort, children are the greatest trust that God has given to every parent in the world. Therefore, children are the responsibility of parents. A child's future depends in part on the parenting and education provided by parents. Children are entrusted by God, as entrusted to them, parents who are entrusted must take good care of their entrusted care, by taking care of them and providing everything that will ensure that the entrusted care is maintained and in accordance with the wishes of the entrusted person to the entrusted person. As the most perfect creature, humans were chosen by Allah as caliphs on this earth. As a caliph, it is a must to understand everything that is entrusted to us on this earth by Allah, including knowing and carrying out our trust as a parent to our children. Taking care of all the needs of children from the moment they are born is part of a parent's obligation, but regarding human responsibilities on this earth, to fill, maintain and preserve nature on this earth requires knowledge and skills. In fact, humans are also servants created by Allah to worship and adore Allah. Therefore, as a parent, it is your responsibility to guide your children to implement and realize their goals and responsibilities as servants.